Genetic evidence indicates the occurrence of the Endangered Kashmir musk deer Moschus cupreus in Uttarakhand, India. Issue 3 (31st May 2022) - Kumar, Ajit; Singh, Bhim; Sahoo, Subhashree; Gautam, Kumudani Bala; Gupta, Sandeep Kumar
Abstract: The Endangered Kashmir musk deer Moschus cupreus occurs in the western Himalayan region from Nepal to Afghanistan, but there is a lack of comprehensive and reliable information on its range. The region also harbours the Endangered Himalayan musk deer Moschus leucogaster, and this range overlap may have led to misidentification of the two musk deer species and errors in the delimitation of their ranges. Here, using genetic analysis of the mitochondrial DNA control region, we examined the phylogenetic relationship among musk deer samples from three regions in India: Ganderbal District in Jammu and Kashmir, and Kedarnath Wildlife Sanctuary and Nanda Devi Biosphere Reserve, both in Uttarakhand. The Bayesian phylogenetic analysis indicated a close genetic relationship between samples from Jammu and Kashmir, Kedarnath Wildlife Sanctuary and Nanda Devi Biosphere Reserve, validated by previously published sequences of Kashmir musk deer from Nepal. Our analyses confirmed the samples from Uttarakhand to be from the Kashmir musk deer, which was not previously known from this region. Therefore, we recommend further research in this area, to validate species identification and confirm the geographical distribution of the various species of musk deer. In addition, we recommend revision of the range of M. cupreus in the IUCN Red List assessment, to facilitate effective conservation and management of this Endangered species.